Second-line salvage chemotherapy for transplant-eligible patients with Hodgkin’s lymphoma resistant to platinum-containing first-line salvage chemotherapy - Villa, Diego (Ferrata Storti Foundation, 2012)
BACKGROUND: The management of patients with relapsed or refractory Hodgkin’s lymphoma who achieve less than a partial response to first-line salvage chemotherapy is unclear. The objective of this study was to evaluate response and outcomes to second-line salvage and autologous stem cell transplantation in patients not achieving a complete or partial response to platinum-containing first-line salvage chemotherapy. DESIGN AND METHODS: Consecutively referred transplant-eligible patients with relapsed/refractory Hodgkin’s lymphoma after primary chemotherapy received gemcitabine, dexamethasone, and cisplatin as first salvage chemotherapy. Those achieving a complete or partial response, and those with a negative gallium scan and stable disease with bulk <5 cm proceeded to high-dose chemotherapy and autologous stem cell transplantation. Patients with progressive disease or stable disease with a positive gallium scan or bulk ≥5 cm were given second salvage chemotherapy with mini-BEAM (carmustine, etoposide, cytarabine, melphalan). Patients who responded (according to the same definition) proceeded to autologous stem cell transplantation. RESULTS: One hundred and thirty-one patients with relapsed/refractory Hodgkin’s lymphoma received first-line salvage gemcitabine, dexamethasone, and cisplatin; of these patients 99 had at least a partial response (overall response rate 76%). One hundred and twelve (85.5%) patients proceeded to autologous stem cell transplantation, while the remaining 19 (14.5%) patients received mini-BEAM. Among these 19 patients, six had at least a partial response (overall response rate 32%), and nine proceeded to autologous stem cell transplantation. The remaining ten patients received palliative care. Seven of the nine patients transplanted after mini-BEAM had a subsequent relapse. Patients receiving second salvage mini-BEAM had poor outcomes, with a 5-year progression-free survival rate of 11% and a 5-year overall survival rate of 20%. CONCLUSIONS: Patients who require a second salvage regimen to achieve disease control prior to autologous stem cell transplantation have a relatively poor outcome and should be considered for alternative treatment strategies.